The Effects Of 2-Hydroxy Chalcone and its Derivative on The Larvae and Adults of Tribolium Confusum - AL-Sinjari, Sofyan H.S.; Mustafa, Asaad M.; Ahmed, Basim S.; Al-sindi, Dilsher A.M. (Science Journal of University of Zakho, 2019)
2-Hydroxy Chalcone and its derivatives (compounds 1and 2) were used in a toxicity test on the larvae and adults of confused flour beetle Tribolium confusum (Du Val). Mortality tests were done by applying different concentrations (0.01, 0.02 and 0.04 ppm) on 2-Hydroxy Chalcone and its derivatives which were exposed by topical application with 5 µL of each compound and the data were recorded after 24 h of treatments. The mortality % of [7-Hydroxy-9-(pyridine-4-yl)-6H-benzo[C]chromen-6-one] in (compound 2) were 26.6, 50 and 76.67% and 16.67, 36.67 and 63.3% and 13.3, 23.3 and 36.6 % to 3rd, 5th instar larvae and adults, respectively. While in [ 3-thinyl-1-(2-hydroxynaphthyl) -1-propene] (compound 1), the mortality % were 23.3, 40 and 66.6% and 13.3, 30 and 56.6% and 6.6, 16.6 and 26.6 % to 3rd, 5th instar larvae and adults, respectively. The results indicated that (comp.2) was the most toxic one and (comp.1) was the least toxic to confused flour beetle when applied singly. The calculated LC50 values to (compound 2) were 0.019, 0.028 and 0.074 ppm to 3rd, 5th instar larvae and adults, respectively. While to (compound 1), the LC50 values were 0.025, 0.034 and 0.106 ppm to 3rd, 5th instar larvae and adults, respectively. The order of toxicity of the chemical compounds was 2 > 1. These chemical compounds can be used to control confused flour beetle.